Solution-focused approaches in adult mental health research: A conceptual literature review and narrative synthesis - Jerome, Lauren; McNamee, Philip; Abdel-Halim, Nadia; Elliot, Kathryn; Woods, Jonathan (Frontiers in Psychiatry, 2023)
Solution-focused approaches are one approach to treatment used in a wide variety of settings in modern mental healthcare services. As yet, there has been no overall synthesis of how this approach is understood in the adult mental health literature. This conceptual review aimed to synthesise the ways that solution-focused approaches have been conceptualised and understood, within the adult mental health literature, in the five decades since their conception. A systematic search followed by multiple techniques from the narrative synthesis approach were used to develop a conceptual framework of the extracted data. 56 papers published between 1993 and 2019 were included in the review. These papers spanned a variety of clinical contexts and countries, but despite this the underlying key principles and concepts of solution-focused approaches were remarkably similar over time and setting. Thematic analysis of extracted data outlined five key themes relevant to the conceptualisation of this approach. This conceptual framework will help support clinicians using solution-focused techniques or therapies by giving them a coherent understanding of such approaches, by what mechanisms they work, and how key principles of this approach can be utilised in adult mental health settings.